The (Arab) Agricultural Investment for Development Analyzer (AIDA): An innovative tool for evidence-based planning - Raouf, Mariam; Kassim, Yumna; Kurdi, Sikandra; Mogues, Tewodaj; Mahmoud, Mai; Randriamamonjy, Josee; Thurlow, James; Wiebelt, Manfred; Breisinger, Clemens (International Food Policy Research Institute, 2018)
This paper describes an innovative agricultural and rural economic planning tool that will help governments and analysts in the design of agricultural investment plans: the (Arab) Agricultural Investment for Development Analyzer (AIDA). A policy challenge for all governments, including those in the Middle East and North Africa, is determining the appropriate allocation and quality of public spending to foster agricultural and rural economic growth, employment creation, and poverty reduction. The AIDA economic planning toolkit has been built using an economy-wide and minimalistic investment data approach to assist governments in meeting this planning challenge. Centered on the use of economy-wide Computable General Equilibrium (CGE) models, it allows for a comprehensive planning approach to ensure that the level and allocation of investment in the agriculture and rural sectors is sufficient for achieving desired targeted outcomes. It does this by linking agricultural and rural spending to economic growth, job creation, and household poverty, given resource and market constraints, as well as considering trade-offs and opportunity costs associated with different investment options. Such a holistic system approach enables the ranking of possible interventions and allocations of public funds amid possible changes in public policy to help in designing national agriculture plans and targets.